Effect of TGF-β1 Stimulation on the Secretome of Human Adipose-Derived Mesenchymal Stromal Cells - Rodríguez, Tania M. (Stem Cells Transl Med, 2015)
Adipose tissue is an attractive source of mesenchymal stromal cells (MSCs) owing to the relative ease of obtaining large volumes with more MSC abundance compared with other sources. Increasing evidence supports the fact that trophic factors secreted by MSCs play a pivotal therapeutic role. Several strategies in regenerative medicine use MSCs, mainly exploiting their immunosuppressive effect and homing capacity to sites of damage. Transforming growth factor-β1 (TGF-β1) is a pleiotropic cytokine that, depending on the cell niche, can display either anti-inflammatory or proinflammatory effects. TGF-β1 expression increases in various tissues with damage, especially when accompanied by inflammation. Thus, we analyzed the effect of TGF-β1 on the secretion by adipose-derived mesenchymal stromal cells (ASCs) of a panel of 80 cytokines/chemokines using an antibody array. To avoid a possible effect of fetal bovine serum (FBS) on ASCs secretion, we performed our analysis by culturing cells in FBS-free conditions, only supplemented with 0.1% of bovine serum albumin. We report the cytokine profile secreted by ASCs. We also found that TGF-β1 exposure modulates 8 chemokines and 18 cytokines, including TGF-β1 and -β2, and other important cytokines involved in immunosuppression, allergic responses, and bone resorption. SIGNIFICANCE: Mesenchymal stromal cells (MSCs) secrete a broad spectrum of bioactive macromolecules that are both immunoregulatory and serve to structure regenerative microenvironments in fields of tissue injury. Increases or decreases in the production of TGF-β1 have been linked to numerous disease states, including autoimmune diseases and cancer. The secretome of MSCs stimulated with TGF-β1 is largely unknown. Thus, the present study makes an important contribution toward a better understanding of how MSCs could be affected by a cytokine normally upregulated in various diseases.